2015
DOI: 10.1016/j.rser.2015.07.175
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of renewables portfolio standards in the United States

Abstract: As state-level renewable portfolio standards (RPS) have driven large increases in U.S. renewable generation capacity, states have sought to quantify the costs and benefits of these policies. This paper examines recent costs and benefits of RPS implementation, focusing on the net (or incremental) cost to utilities of renewables used for compliance with RPS targets during the years 2010-2012. Incremental RPS cost estimates are developed using a wide variety of methods and assumptions, which makes comparisons amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 16 publications
0
53
0
Order By: Relevance
“…23 suggested that the use of fossil fuels should be reduced, and renewable fuels should be deployed as replacement for fossil fuels for environmental and social benefits. 23,24 Many alternative energy resources for fossil fuels are available worldwide. Fuels are employed to produce heat, mechanical work, and power generation for subsequent use in people's daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…23 suggested that the use of fossil fuels should be reduced, and renewable fuels should be deployed as replacement for fossil fuels for environmental and social benefits. 23,24 Many alternative energy resources for fossil fuels are available worldwide. Fuels are employed to produce heat, mechanical work, and power generation for subsequent use in people's daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…The minimization of losses was done via an iterative process to minimize the objective function in Eqn. (3). This reaction zone thickness that minimizes the sum of losses is then used to calculate the ohmic potential drop and charge transfer overpotential.…”
Section: Bottom-up Model Developmentmentioning
confidence: 99%
“…Renewable generation, comprising hydropower, wind, solar, geothermal, and biomass, contributed to 23% of global electricity generation by the end of year 2013 at greater than 5000 TW h, and power capacity of slightly less than 1600 GW [1] with hydropower generation comprising 17% [2]. Renewable portfolio standard policies in the USA are implemented by 29 states, with renewable electricity generation mandates of 15 to 50% by the years 2020 to 2030 [3].…”
Section: Introductionmentioning
confidence: 99%
“…They have been one of the policy drivers for RE growth in the United States, along with federal tax incentives and other forms of state-level support (Leon 2015). Collectively, 58% of all non-hydroelectric RE capacity built in the United States from 1998 through 2014 is being used to meet RPS requirements (Barbose 2015). In aggregate, existing state RPS policies require that by 2025, at which point most RPS requirements will have reached their maximum percentage targets, at least 8% of total U.S. generation supply will be met with RPS-eligible forms of renewable electricity, equivalent to roughly 106 gigawatts (GW) of renewable generation capacity (Wiser and Bolinger 2015).…”
Section: Introductionmentioning
confidence: 99%